2021
DOI: 10.3390/pr9020207
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of Different CO2 Capture Technologies for Coal to Ethylene Glycol Process

Abstract: The coal to ethylene glycol (CTEG) process has drawn much attention due to the serious conflict between supply and demand of ethylene glycol in China. However, it is inevitably accompanied by the problem of high CO2 emissions. Carbon capture is one of the most promising potential effective ways to address this issue. However, the CTEG process, integrated with carbon capture technology, will lead to energy and economic penalties. Thus, a comprehensive evaluation of CTEG process with different CO2 capture techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 33 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Here, the total production costs (TPC) of different CO 2 synthesis methanol technologies were evaluated to compare the economic performances of different methanol synthesis processes. The formulas are shown as follows: T P C = k T C R k + prefix∑ k C O M k prefix∑ k C k m MeOH T C R k = T C I k × C R F C R F = r 1 false( 1 + r false) n where TCR k is the total investment required for unit k ; COM k is the annual operation and maintenance cost of unit k ; C k is the salvage value of unit k (4%); m MeOH is the methanol flow rate; CRF is the capital recovery factor; and r and n are, respectively, the depreciation rate (12%) and the life time of the plant (15%). Raw material costs (CR), utility costs (CU), and operation and maintenance costs ( CM ) were calculated based on data in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the total production costs (TPC) of different CO 2 synthesis methanol technologies were evaluated to compare the economic performances of different methanol synthesis processes. The formulas are shown as follows: T P C = k T C R k + prefix∑ k C O M k prefix∑ k C k m MeOH T C R k = T C I k × C R F C R F = r 1 false( 1 + r false) n where TCR k is the total investment required for unit k ; COM k is the annual operation and maintenance cost of unit k ; C k is the salvage value of unit k (4%); m MeOH is the methanol flow rate; CRF is the capital recovery factor; and r and n are, respectively, the depreciation rate (12%) and the life time of the plant (15%). Raw material costs (CR), utility costs (CU), and operation and maintenance costs ( CM ) were calculated based on data in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Although it requires intensive regeneration energy and high operating cost, it offers high CO 2 removal, and it has a high capacity at low pressure . To efficiently capture the CO 2 from the produced syngas, the methanol absorption method is a superb technology as an acid gas removal (AGR) unit …”
Section: Introductionmentioning
confidence: 99%
“… 25 To efficiently capture the CO 2 from the produced syngas, the methanol absorption method is a superb technology as an acid gas removal (AGR) unit. 26 …”
Section: Introductionmentioning
confidence: 99%
“…It is found that the particle-based Archimedes number has a linear relationship with the solid holdup at all operating conditions. Ma et al [6] compare different CO 2 capture technologies for the coal to ethylene glycol process. These include Rectisol, mono-ethanol amine (MEA), chilled ammonia process (CAP) and dimethyl carbonate (DMC) technologies.…”
mentioning
confidence: 99%